2020
DOI: 10.1007/s12016-020-08785-7
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Mast Cells and Adipocytes in Physiologic and Pathologic Conditions

Abstract: Excessive fatty acids and glucose uptake support the infiltration of adipose tissue (AT) by a variety of immune cells including neutrophils, pro-inflammatory M1 macrophages, and mast cells (MCs). These cells promote inflammation by releasing proinflammatory mediators. The involvement of MCs in AT biology is supported by their accumulation in the AT of obese individuals along with significantly higher serum levels of MC-derived tryptase. AT-resident MCs under the influence of locally derived adipokines such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 88 publications
2
20
0
2
Order By: Relevance
“…Among the various resident cellular targets for leptin stimulation in vivo , we identified mast cells as a key cell population. Importantly, our results identify mast cells as modulators of leptin-driven eosinophilic reaction are in line with recent postulations that adipose tissue resident mast cells or the obesity-related increased mast cell population are modulators of adipose tissue homeostasis and inflammation ( 60 , 61 ).…”
Section: Discussionsupporting
confidence: 91%
“…Among the various resident cellular targets for leptin stimulation in vivo , we identified mast cells as a key cell population. Importantly, our results identify mast cells as modulators of leptin-driven eosinophilic reaction are in line with recent postulations that adipose tissue resident mast cells or the obesity-related increased mast cell population are modulators of adipose tissue homeostasis and inflammation ( 60 , 61 ).…”
Section: Discussionsupporting
confidence: 91%
“…So, further experiments demonstrated that c-kit ablation but not mast cell depletion is what improves the metabolic profile in mice (53). Although more genetic models explored the effect of the absence of mast cells in WAT, the current evidence is that it does not protect from obesity and insulin resistance (54,55). In a nutshell, mast cells are not critical players driving adipose tissue inflammation in patients with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells infiltrate the adipose tissue in the early stage of obesity and influence adipocytes behavior and function by secreting IFN-ϒ and IL-6 [ 50 , 51 ]. The dendritic cells, which are professional antigen-presenting cells, may stimulate Th17 response by aiding in the chemoattraction of macrophages and neutrophils in the obese adipose tissues [ 52 ].…”
Section: Inflammation As a Part Of Obesitymentioning
confidence: 99%